THE ROLE OF MOTIVATION IN SECOND LANGUAGE ACQUISITION - Karimberganova Shahnoza Muxammad qizi,; Ruzmetova Diana Kamilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Motivation is considered one of the most salient psychological constituents that significantly  affect  second  language  acquisition.  Indeed,  motivation  significantly determines the extent of involvement, effort, and tenacity that learners must exhibit in the  language  learning  process.  Moreover,  the  abstract  touches  upon  the  roles  of different internal and external factors that play a pivotal role in shaping motivation, such  as  the  attitude  of  learners,  learning  environments,  instructors,  their  cultural experiences, as well as their own goals. Recent studies show that learners with strong motivation  usually  demonstrate  greater  language  competence  in  reading,  writing, listening, as well as speaking skills, as this component significantly affects the practice carried  out  by  learners.  This  study  accentuates  that  motivation  remains  a  dynamic component that keeps on fluctuating, and instructors must use different motivational techniques in order to establish positive environments.